Tailored chiral phosphoramidites support highly enantioselective Pd catalysts for asymmetric aminoalkylative amination - Suchen Zou; Zeyu Zhao; Guoqing Yang; Hanmin Huang (Nature Communications)
Abstract Even though tuning electronic effect of chiral ligands has proven to be a promising method for designing efficient catalysts, the potential to achieve highly selective reactions by this strategy remains largely unexplored. Here, we report a palladium-catalyzed enantioselective ring-closing aminoalkylative amination of aminoenynes enabled by rationally tuning the remote electronic property of 1,1’-binaphthol-derived phosphoramidites. With a tailored 6,6’-CN-substituted 1,1’-binaphthol-derived phosphoramidite as a ligand, a broad range of aromatic amines are compatible with this reaction, allowing the efficient synthesis of a series of enantioenriched exocyclic allenylamines bearing saturated N-heterocycles with up to >99% enantiomeric excess. Remarkably, a one-pot aminoalkylative amination/hydroamination process for the rapid synthesis of chiral spirodiamines promoted by this catalytic system is also established. Detailed mechanistic studies provide solid evidence to support that the remote electronic character of these chiral ligands can efficiently tuning the enantioselectivity by altering the length of the allylic C-Pd bond of the key catalytic intermediate.